Determination of Chlorophyll-A Concentration from Seawifs Data in the South China Sea - Asmat, Arnis (2001)
The use of satellite remote sensing to provide synoptic measurements of the ocean is becoming increasingly important in the fishing industry. The evolving capabilities of satellite sensors and data processing techniques provide a promising tool towards the development of fish forecasting and management techniques. Mapping phytoplankton distribution and growth are important in fisheries and physical oceanographic studies. The light absorbing pigments collectively known as chlorophyll-a are commonly used by oceanographers as an index of phytoplankton concentration. The objective of this study is to measure the concentration of chlorophyll-a in the Exclusive Economic Zone (EEZ) of East Coast Peninsular Malaysia, based on remotely sensed data. In order to achieve this objective it is essential to determine an empirical relation between the chlorophyll-a and the radiances values recorded by the sensor and to measure the concentration chlorophyll-a from remotely sensed data. This study used in-situ data of concentration chlorophyll-a to measure the concentration of chlorophyll-a from SeaWiFS data. Models to estimate the chlorophyll-a concentration were generated by computation based on empirical method using radiance ratio of SeaWiFS channels. The data from the sea truth campaigned of 24th August 2000 until 29th August 2000 were applied to obtain the correlation between chlorophyll-a concentration (mg/m3) and the radiance values in chosen channel of SeaWiFS. The amount of concentration of chlorophyll-a was calculated based on blue, blue-green and green (442nm, 490nm and 555nm) reflectance ratios, this was done by selecting representative radiance values corresponding to in-situ data measurements. The study proved that the remote sensing technique is a very useful tool for studying chlorophyll-a distribution in a large water body area such as the- EEZ. In this work, channel 2, channel 3 and channel 5 of SeaWiFS data have been found to be the most suitable channel to extract the chlorophyll-a concentration. Correlation analysis between remotely sensed data and chlorophyll-a in-situ data indicates the possibility of mapping chlorophyll-a concentration with some degrees of success. The strong correlation of radiance ratio corresponding to above channel with in-situ data provides the basis for the development of equation and constant for the estimation of chlorophyll-a concentration in South China Sea.